Aplikasi kontrak al-kafalah dalam produk-produk pembiayaan perdagangan antarabangsa Islam - Abdul Rahim, Ahmad Khilmy; Mohamed Naim, Asmadi; Zainol, Zairani (Kolej Universiti Islam Sultan Azlan Shah, 2015)
Islamic Trade Finance (ITF) instruments were introduced into the Islamic banking system in Malaysia since the early 1990s when there was a need for Islamic instruments in commerce especially in international trade.Most of the financial products are based on conventional instruments such as Bank Guarantee (BG), Letter of Credit (LC), Accepted Bill (AB), Shipping Guarantee (SG), Export Credit Refinancing (ECR) and others.In order to be accepted in Islamic Finance, some amendments will have to be made so that it will be ‘sharia compliant’ by applyingmuamalat contracts to those products. Muamalat contracts that are widely used in Islamic Trade Finance products are murabahah, bay’ al-dayn, kafalah and wakalah.This article analyses the views of previous and contemporary Islamic scholars and those with authority in Islamic financial jurisprudence in the use of kafalah contracts. This article also analyses the issues that arise in the application of kafalah in Islamic Trade Finance products namely Shipping Guarantee-i (SG-i) and Bank Guarantee-i (BG-i).